Learning of Entrepreneurship and Entrepreneurship Practices Against Business Interest - Nita Kanya (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Entrepreneurship education is something that is needed for children and society. Because it is beneficial to the operational efforts of the national development program, priority needs to be included in the contents of the school curriculum. This study aims to determine the magnitude of the effect of Entrepreneurship Learning Entrepreneurial interest, in the 2015 class of Langlangbuana University FEB Students. Qualitatively through questionnaire data collection techniques obtained from FEB Langlangbuana University students class of 2015. To test the data of this study using the software in the form of SEM PLS. The results of this study indicate that t is seen that the value of Entrepreneurship Learning (2,314) is greater than tcritical (1.96) which means that the results of hypothesis 1 are H0 rejected, then the statistical conclusion is that Entrepreneurship Learning significantly influences entrepreneurial interest. Then, on the entrepreneurial practice variable that the calculated value of Entrepreneurship Practices (2,378) is greater than tcritical (1.96) which means that the results of hypothesis 1 are H0 rejected, then the statistical conclusion is that Entrepreneurial Practices significantly influence entrepreneurial interest.